Jihad dinamis: menelusuri konsep dan praktik jihad dalam sejarah Islam - Zakiya Darajat (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2016)
Being the most misunderstood term, jihad has been misconstrued by orientalists and Muslims alike. The misconception of jihad can be attributed to not only severely substantialist or textualist reading of the Qur’an and Hadith, but also misinterpretation of the history of jihad being in practice during the early generation of Muslims. The comprehensive reading of texts on jihad in the Qur’an and Hadith has to be accompanied by an accurate and objective reading on how jihad was put in practice by the Prophet  Muhammad, the Companions and the Successors, and then how it was practiced during the subsequent periods (medieval, modern and contemporary), particularly in order to know in which context jihad has been regarded as a spiritual, ethical and moral struggle (jihad akbar), and in what kind of context it has been practiced as a physical struggle in a war (jihad asghar). In that way, jihad would not be misunderstood and, on the contrary, be appropriately connected with its contexts. The dynamics of the implementation of jihad has been influenced by different socio-historical factors, such as political realities facing Muslims in different periods. This essay seeks to explore how the practice of jihad has changed over time in Muslim history, from the time of the Prophet to the modern day Indonesiamarked by vibrant Muslim movements.